Experimental research in the fire resistance of the double-frame container. (July 2020) - Mu, Dong; Wu, Song; Zeng, Fei; Wang, Fengjun; Huang, Xin
Abstract: During the road transportation of hazardous materials (hazmat), container was usually used to protect the inner package from accidents. The conventional container is a sandwich-framed construction. When it was subjected to car fire, the combustible materials such as poly-foam interlayer would burn up in few minutes. Once the hazmat leaked out, it could result in the great loss of the public and environment. In this paper, a double-frame container mechanism was firstly proposed for loss prevention. In order to investigate the heat conduction pattern and the effect of interlayer thickness, the two-dimensional (2D) Finite Element (FE) model was developed. Based on the numerical results, the interlayer thickness was defined as 155 mm considering the ignorance of sealing. Furthermore, two small-scale containers whose interlayer were ceramic fiber and phenolic foam separately were manufactured. Pool fire experiments were carried out to evaluate the fire resistance of the mechanism and compare the insulation of the interlayer. Results show that the construction of the container remained complete after about 30-min fire exposure. The maximum temperature inside was below 100 °C during the burning process. When the fire burnt down, the temperature inside increased to 110 °C and then declined gradually during the 1000-min cooling process. Additionally, although the thermal insulation of the container with phenolic foam is relatively better, the ceramic fiber is much more suitable for the interlayer considering the sealing of the container and the stability in heat. In summary, the double-frame container could protect the product inside from car fire. It could be beneficial for the fire-resistant design of much bigger containers, which might be widely used for loss prevention in hazmat transport. Highlights: A double-frame container mechanism with three-state sealing mechanism was developed. In the 30-min burning progress, ceramic fiber showed better fire resistance than phenolic foam. The study on small-scale container could be beneficial for the fire-resistant designing of much bigger fire-resistant containers.